Meteoric water effect of diagenesis processes in deep carbonate reservoirs - Wang, Zhen; Zhang, Yiqiong; Wang, Xueke; Lin, Yaping; Jiang, Li; Zhang, Xiaozhen (Frontiers in Earth Science, 2024)
As a major oil and gas resource in the world, deep carbonate reservoirs have enormous exploration and development potential. However, due to its complex diagenetic process, it has brought great difficulties to development and exploration. During the formation process of carbonate oil and gas reservoirs, the effect of atmospheric precipitation forms karst caves, but its complex internal mechanism seriously restricts the exploration and development of carbonate oil and gas reservoirs. Taking the deep carbonate reservoir in the Tarim Basin as the research object, this paper studies the diagenetic process of the deep carbonate reservoir through geological survey, and analyzes the impact of atmospheric precipitation on the porosity and mineral changes of the carbonate reservoir in different diagenetic stages by using indoor experiments, theoretical analysis, and numerical simulation research methods, and draws the conclusion that atmospheric precipitation has an impact on the reservoir minerals and porosity. The research results provide theoretical data support for guiding the exploration of deep carbonate reservoirs.